Plasma source and loss at comet 67P during the Rosetta mission - Heritier,K; Galand,M; Henri,P; Johansson,FL; Beth,A; Eriksson,AI; Vallières,X; Altwegg,K; Burch,JL; Carr,C; Ducrot,E; Hajra,R; et al. (Astronomy and Astrophysics, 2018)
Context.The Rosetta spacecraft provided us with a unique opportunity to study comet 67P/Churyumov-Gerasimenko from a closeperspective and over a two-year time period. Comet 67P is a weakly active comet. It was therefore unexpected to find an active anddynamic ionosphere where the cometary ions were largely dominant over the solar wind ions, even at large heliocentric distances.Aims.Our goal is to understand the different drivers of the cometary ionosphere and assess their variability over time and over thedifferent conditions encountered by the comet during the Rosetta mission.Methods.We used a multi-instrument data-based ionospheric model to compute the total ion number density at the position ofRosetta. In-situ measurements from the Rosetta Orbiter Spectrometer for Ion and Neutral Analysis (ROSINA) and the Rosetta PlasmaConsortium (RPC)–Ion and Electron Sensor (IES), together with the RPC–LAngmuir Probe instrument (LAP) were used to computethe local ion total number density. The results are compared to the electron densities measured by RPC–Mutual Impedance Probe(MIP) and RPC–LAP.Results.We were able to disentangle the physical processes responsible for the formation of the cometary ions throughout thetwo-year escort phase and we evaluated their respective magnitudes. The main processes are photo-ionization and electron-impactionization. The latter is a significant source of ionization at large heliocentric distance (>2 au) and was predominant during the lastfour months of the mission. The ionosphere was occasionally subject to singular solar events, temporarily increasing the ambientenergetic electron population. Solar photons were the main ionizer near perihelion at 1.3 au from the Sun, during summer 2015.